Explaining the difference between the predictive power of value orientations and self-determined motivation for proenvironmental behavior. (February 2021) - Masson, Torsten; Otto, Siegmar
Abstract: Previous research has shown that biospheric, altruistic, and egoistic values explain more variance in proenvironmental behavior than explained by the self-determined motivation that is linked to such behavior (i.e. motivation fueled by the fulfilment of basic psychological needs). However, these findings might stem from the relatively narrow measures of proenvironmental behavior employed in these studies. In two studies, we investigated the predictive power of self-determined motivation and value orientations in explaining broader measures of self-reported proenvironmental behavior. Our results support our expectation that self-determined motivation would remain a significant predictor of proenvironmental behavior after controlling for value orientations. In line with our expectations, self-determined motivation (vs. values) was more predictive of behavior that was predominantly guided by environmental motives. We discuss the implications of these results for the prediction of proenvironmental behavior. Highlights: Self-determined motivation can explain proenvironmental behavior better than values Broader measures of proenvironmental behavior can help build consistent theory Self-determined motivation better explains behavior guided by environmental motives